Some remarks on the contacts between the Greek and the Hallstatt culture considering the area of the northern Croatia - Potrebica, Hrvoje (Array, 1997)
The rich Hallstatt groups from the neighboring Slovenia shows the clear connection with the Etruscan cultural influences that were transferred through the Alpine region deep in the central area of the Hallstatt culture. These influences are visible in the concrete imported material, but maybe even more in the artistic ideas that were taken, transformed and adapted to the taste of the Hallstatt culture. In part of Croatia that goes from Slovenia, over the southern end of the Pannonian plain, north of the river Sava, during the Iron Age exists yet another cultural group (the Martijanec-Kaptol group) that seems to be part of the Hallstatt cultural complex, but at the same time it shows clear influences of the regions south of the river Sava, mainly Balkans. The Balkans had its own specific Iron Age cultures but it was also the Greek trade dominion. That is how specific, almost luxury, products of the Greek culture, like bronze vessels and helmets and other defense weapons, reached the Middle Europe. There are three main possible ways by which the imported Greek material could have reached this area from the South: the way from the Black Sea along the Danube, the way along the valley of the river Neretva, and the continental way across Balkans. Although we cannot completely ignore the ways that follow the valleys of the rivers Neretva and Danube, the current state of research and published information suggest the continental way from the South as the most probable solution. There are more variants of that way. The distribution of the Greek import suggests the way that followed course of the future via Egnatia as more probable than the usual variant of that way that followed valleys of Vardar, Morava and Drina. However, the new research results suggest the possibility of the more western way - from the central Greece, across Tesalia to the Lake of Ohrid and further through the valleys of Ibar and Morava. We also shouldn't forget the way from the Greek colonies Apolonia and Dyrachion through the valley of Drim, that also comes out to the valley of Ibar. Beside the direct way from the Greece, there is also possibility that the Greek material came to this area along the same way as the material that shows the Etruscan influences, that is from Italy, across the Alpine region of Slovenia.